Uso de geotecnologia na análise morfométrica das bacias hidrográficas dos rios Barcarena e Itaporanga, município de Barcarena – Nordeste do Pará - CONCEIÇÃO, Yago Augusto Botelho da (2024)
The present work had as objective the study involving the application of geotechnologies in the characterization of the morphometry and the use and land cover of the watersheds of the rivers Barcarena and Itaporanga in Barcarena - Pará. The methodological procedures for the study of the hydrographic basins of the Barcarena and Itaporanga rivers consisted of the following steps: morphometric analysis, definition of land use and cover classes, definition of environmental preservation areas and spatial distribution of precipitation. In the morphometric analysis, the geometric, relief and drainage network characteristics were evidenced. As for the definition of land use and land cover classes, the classes adopted were non-agricultural and agricultural anthropic areas, natural vegetation, water and others. In the areas of environmental preservation, the delimitation of the environmental protection areas (APP's) was carried out along the watercourses and springs following the guidelines of Article 4 of Law 12.651/12 (Brazilian Forestry Code). Finally, in the spatialization of rainfall and the spatialization of the amount of precipitation in the study area, monthly data from the Climate Hazards Group InfraRed Precipitation with Stations (CHIRPS) product developed by the United States Geological Survey (USGS) and by the Climate Hazards Group at the University of California, Santa Barbara (UCSB). Finally, the morphometric analysis showed that the sub-basins of the Barcarena and Itaporanga rivers have a low capacity to form new watercourses, and according to the form factor values associated with the compactness coefficient, they are probably not subject to flooding in normal precipitation conditions.